IMPROVEMENT OF CRYSTAL QUALITY IN SEMIPOLAR GaN LAYER BY USING SELF-ORGANISED NANOMASKS ON M-SAPPHIRE - Ryu, Y; Jeong, J; Jang, J; Lee, K; Min, D; Kim, J; Kim, M; Moon, S; Yoo, G; Nam, O (Journal of Ceramic Processing Research, 2013)
Semipolar GaN layers were grown on SiO2 nanorods, which were fabricated by introducing self-organised masks to reduce defect density and to improve crystal quality (modified epitaxial lateral overgrowth (ELO) method). The decrease in the density of defects such as basal stacking faults, partial dislocations, and perfect dislocations was demonstrated by X-ray rocking curves for various planes. In addition, cross-sectional TEM images also confirmed the role of SiO2 nanorods in blocking the defects. Further, the cathodoluminescence intensity of GaN layers grown on SiO2 nanorods and the internal quantum efficiency of InGaN/GaN double quantum wells on SiO2 nanorods were 9.5 times and 80% higher, respectively, than those of reference GaN layers. These higher values could be attributed to the improvement in the crystal quality of GaN layers due to the introduction of SiO2 nanorods.